Effects of concentration and solvent composition on the electrical conductivity of sodium bromide in pure water and ethanol-water mixed solvent media - Bhattarai, Ajaya; Neupane, Sanjay (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Precise measurements on the conductivity of Sodium Bromide in pure water and ethanol-water mixed solvent media containing 0.10, 0.20, 0.30, 0.40, 0.50 and 0.60 volume fractions of ethanol at room temperature are reported. The concentrations were varied from ~ 0.010 to ~ 0.10 mol.L-1. The results showed a sharp increase in the conductivity with increasing electrolyte concentration. The conductivity of electrolyte decreases with increase in the amount of ethanol. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 1-6 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7318